Koselleck, a história dos conceitos e as temporalidades - Jose D\u2019Assunçao (Universidad de Sevilla, 2016)
This article aims to examine, in a historiographical view and according the perspective of the Theory of History some of the most important contributions of the german historian Reinhart Koselleck. On the one hand, we will seek to delineate the History of Concepts as a historical field particularly important in recent decades. On the other hand, we will examine the considerations of Reinhart Koselleck, co-founder of the new field, concerning his studies around a specific concept: Time. The primary reference is the book Future Past, written by Koselleck in 1979 –an essay in which one the german historian establish his main considerations about the three levels of temporality– Past, Present and Future –using the concepts of “experience space” and “horizon of expectation”.